Banded Sleeve Gastrectomy Improves Weight Loss Compared to Nonbanded Sleeve: Midterm Results from a Prospective Randomized Study - Paolo Gentileschi; Emanuela Bianciardi; Leandro Siragusa; Valeria Tognoni; Domenico Benavoli; Stefano D’Ugo (Journal of Obesity, 2020)
Background. Weight regain after laparoscopic sleeve gastrectomy (LSG) is nowadays a growing concern. Sleeve dilatation and loss of food restriction is considered the main mechanism. The placement of a silicon ring around the gastric tube seems to give benefits in the short term. We report the results of a randomized study comparing LSG and laparoscopic banded sleeve gastrectomy (LBSG) over a 4-year follow-up. Objectives. To evaluate the efficacy of banded sleeve gastrectomy compared to standard sleeve in the midterm. Methods. Between 01/2014 and 01/2015, we randomly assigned 50 patients to receive one of the two procedures. Patients’ management was exactly the same, apart from the band placement. We analyzed differences in weight loss, operative time, complication rate, and mortality, with a median follow-up of 4 years. Results. Twenty five patients were assigned to receive LSG (Group A) and 25 LBSG (Group B). The mean preoperative BMI (body mass index) was 47.3 ± 6.58 kg/m2 and 45.95 ± 5.85 kg/m2, respectively. There was no significant difference in the operative time. No intraoperative or postoperative complications occurred. At 12-month follow-up, the mean BMI was 29.72 ± 4.40 kg/m2 in Group A and 27.42 ± 4.47 kg/m2 in Group B (p=0.186). After a median follow-up of 4 years, the mean BMI in Group B was significantly lower than Group A (24.10 ± 4.52 kg/m2 vs 28.80 ± 4.62 kg/m2; p=0.00199). Conclusions. LBSG is a safe procedure, with no impact on postoperative complications. The banded sleeve showed a significant greater weight loss in the midterm follow-up. Considering the issue of weight regain observed after LSG, the placement of a perigastric ring during the first procedure may be a strategy to improve the results. This trial is registered with NCT04228185.